muSR Study on the Electron Transfer Mechanism of a Blue Copper Protein, Pseudoazurin - Dr Amba Datt Pant; Professor Eiko Torikai; Professor Takamitsu Kozuma; Professor Kanetada Nagamine; Professor Yoko Sugawara; Dr Iinuma Fukao; Professor Koichiro Shimomura; Dr Katsu Ishida; Mr Yuga Nakazawa (ISIS Facility, 2019)
In order to establish the method to apply polarized muon for study of biological functions and life sciences, we need to perform systematic study to know the behavior of muon in bio-molecules and know what information can be extracted from the implantation of muon in different macromolecules. Here we propose to study the electron transfer mechanism in blue Copper protein - Pseudoazurin(PAz) using muon. The PAz has single-copper ion binding site that serves as an electron mediator between large proteins. We will study the behavior of muon in both reduced and oxidized forms of PAz along with apoPAz (without Copper center) and buffer (as a reference). It is expected that the muon/muonium signal from PAz (reduced and oxidized) and comparison with that from apoPAz will help to elucidate the electron transfer mechanism in the blue Copper protein.
Keywords: STFC ISIS Neutron and Muon Data